Draft Annual Plan 1993-94 Union Territory of Chandigarh - Planning Commission (Planning Commission, 1993)
Chandigarh is a small Union Territory without legislature, and is spread over an area of 114 Sq. Kms., comprising the city of Chandigarh, Notified Area Committee, Manimajra and 22 Villages. The population as per 1991 census of this Union Territory is approximately 6.41 lakhs out of which, 87,000 is the Rural population. The Urban Rural population ratio is 86:14. This is against the All India Ratio of 24:76. Due to compactness of the U.T., there exists a close rapport between the people and the Chandigarh Administration and as such no difficulty is faced in the identification of the problems of this area.
Planning and Evaluation Organisation Finance Department Chandigarh Administration